Implementasi Public Private Partnership dalam Pengembangan Pariwisata di Kabupaten Toraja Utara - Djabbari, Muhammad Hidayat; Alwi, Alwi; Thamrin, Saddam Husain (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2021)
The concept of Public Private Partnership (PPP) provides efficiency and Effectiveness in providing public services to the community, as well as helping the government sector deal with limited budget and resources in developing the tourism sector. This study aims to determine how the implementation of the Public Private Partnership (PPP) in tourism development in North Toraja Regency. This research uses a qualitative approach. Data collection was carried out by interview, observation and documentation study. Data processing techniques and data analysis were carried out in three stages, namely: data reduction, presentation and conclusion drawing. The informants in this study were: (a) the Culture and Tourism Office of North Toraja Regency; (b) Owner / Manager of Ke'te Kesu 'and Lempe Negeri Diatas Awan Tourism Object; (c) Visitors / Community. The results showed: (1) Equity shows the existence of a win-win solution in the distribution of cooperation which has an impact on receiving fees and tourism services; (2) The Effectiveness of this MoU (cooperation agreement) is seen to be effective in receiving revenue (retribution) and providing services to visitors or tourists; (3) The efficiency in this public-private collaboration shows that the use of resources in the development of tourist objects is proven to be more efficient with the involvement of the private sector; (4) Exportability shows the government gets a high risk of demand to meet the needs of tourist objects and compensation to communities affected by the construction of tourist attraction facilities and infrastructure.